COMPARATIVE ANALYSIS BETWEEN SET’S CHARACTER IN GODS OF EGYPT STORY MYTH AND GODS OF EGYPT MOVIE - Nuril Hidayati; Aria Adi Saksi (JURNAL LITERASI, 2022)
This research analyzed the differences and similarities between Gods of Egypt movie and Gods of Egypt Story myth that focus in Set’s character. The theory on translation techniques was based on Five-Factor Theory that included Extraversion, Neuroticism, Openness, Agreeableness and Conscientiousness. This research the researcher chooses descriptive qualitative method to describe comparative between Set’s Character in God of ancient Egypt story myth and Gods of Egypt movie. Gods of Egypt story myth is from The Routledge Dictionary of Egyptian God and Goddesses bookthat published on 2005 and Gods of Egypt movie that released on 2016.The differences between Set’s character in Gods of Egypt story myth and Gods of Egypt movie is there is no Openness to Experience character in Gods of Egypt story myth that showed in Gods of Egypt movie. The Gods of Egypt story myth and Gods of Egypt movie is showed Neuroticism and Conscientiousness but the differences characters are moody, blaming person, selfish, self control, confidence and welcome to the new thing.The similarities character between Gods of Egypt movie and Gods of Egypt story myth are Neuroticism and Conscientiousness such as Irritable or Angry, Jealous and Ambition.